2022
DOI: 10.1186/s12877-022-03041-3
|View full text |Cite
|
Sign up to set email alerts
|

Injuries from falls by older adults in long-term care captured on video: Prevalence of impacts and injuries to body parts

Abstract: Background Falls are the leading cause of injuries in older adults. However, most falls in older adults do not cause serious injury, suggesting that older adults may fall in a manner that reduces the likelihood of impact to body sites that are most vulnerable to injury. In this observational study of falls in long-term care (LTC), we tested whether body parts differed in their probability of impact and injury. Methods We recorded and analyzed video… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…After reviewing the narrative text entries, it became apparent that very few alcohol-related falls on stairs occurred under the age of 15. Given the potential exacerbation of mobility limitations, balance issues and prescription drug interactions, we did not examine injuries among persons aged 65 and older as it would be difficult to fully understand the contribution of alcohol 7. Inter-rater reliability for coding open-ended narrative text ensued as follows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing the narrative text entries, it became apparent that very few alcohol-related falls on stairs occurred under the age of 15. Given the potential exacerbation of mobility limitations, balance issues and prescription drug interactions, we did not examine injuries among persons aged 65 and older as it would be difficult to fully understand the contribution of alcohol 7. Inter-rater reliability for coding open-ended narrative text ensued as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Falls on staircases contribute significantly to the burden of fall-related injuries, with an annual estimate in excess of 1 million emergency department (ED visits annually in the USA 6. While much of the focus on staircase fall injuries has been on the older adult population,7–9 a few studies have examined younger populations and the role of alcohol use 10–15. Alcohol has been found to be associated with TBI among persons who were injured falling on stairs 10 12 14 15.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 1% of all elderly falls result in hip fractures, which significantly increase the risk of morbidity and mortality post-fall [ 4 ]. Furthermore, a study conducted in 2022 over a nine-year period involving 658 residents in a long-term care facility found that falls accounted for over 90% of hip fractures and up to 80% of traumatic brain injuries (TBIs) in older adults [ 5 ]. This review seeks to consolidate and encapsulate the latest insights regarding falls that occur in bed among the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…They are the most common reason for hip fracture hospital admissions (9 in 10 cases). Other injuries that result from falls include head injuries, wrist fractures, humerus, intracranial hematomas, and injuries to internal organs [ 17 ]. In the group of people aged 75 and older, 70% of falls are fatal.…”
Section: Introductionmentioning
confidence: 99%